To rewrite the expression \( 14^{-7} / 9^{-13} \) with only positive exponents, we can apply the property of negative exponents, which states that \( a^{-n} = \frac{1}{a^n} \).
Using this property, we can rewrite the expression as follows:
\[ 14^{-7} / 9^{-13} = \frac{1}{14^7} \cdot \frac{1}{9^{-13}} = \frac{1}{14^7} \cdot 9^{13} \]
Next, we multiply the two fractions together:
\[ = \frac{9^{13}}{14^7} \]
Thus, an equivalent expression to \( 14^{-7} / 9^{-13} \) with only positive exponents is:
\[ \frac{9^{13}}{14^7} \]